Optimization of Initial pH and Total Sugar Concentration Variables on Citric Acid Production from Pineapple Waste with Aspergillus niger Yeast by Using Response Surface Methodology - Widayat, Widayat; Abdullah, Abdullah; Satriadi, H.; Hadi, M. (Jurnal Rekayasa Kimia & Lingkungan, 2011)
Citric acid can be produced from pineapple waste by using fermentation process. This process is done in bubble column reactor with Aspergillus niger yeast. The objective of this research is to find the optimum conditions of initial pH and total sugar concentration. The optimization method used was response surface methodology. This research was carried out at a temperature of 30 oC, spore concentration of 1.23 x 109 spore/ml, total volume 2.0 liter, flow rate of air 58.07 cc/sec and a 5% antifoam concentration. The fermentation process lasted 7 days and the citric acid concentration was analyzed by High Pressure Liquid Cromatography (HPLC) method. Statistica 6 software was used for the data treatment. The mathematical model for the optimization citric acid fermentation in bubble column reactor is Y = 54.507 + 2.9851X - 8.987X12 - 2.581X2 - 15.446X22 - 7.989X1X2 The parameter of Y is citric acid yield, X1 is a coding initial pH and X2 is a coding total sugar concentration. The results has given an initial pH optimum 3.61 and total sugar concentration 19,285% w/v with optimum an yield of 55.03 % .Keywords: Bubble column bioreactor, Citric acid fermentation, Initial pH, Total sugar concentration, Response surface methodology